Non-Maleficence toward Young Kidney Donors: A Call for Stronger Ethical Standards and Associated Factors in Multidisciplinary Nephrology Teams - Mahdi Tarabeih; Wasef Na’amnih (Nursing Reports, 2024)
Background: The rising frequency of live kidney donations is accompanied by growing ethical concerns as to donor autonomy, the comprehensiveness of disclosure, and donors’ understanding of long-term consequences. Aim: To explore donors’ satisfaction with the ethical competence of multi-professional nephrology teams regarding disclosure of donation consequences to live kidney donors. Methods: A cross-sectional study was performed among Israeli live kidney donors who had donated a kidney in two hospitals that belonged to the Ministry of Health’s Transplantation Center one year after the donation, from December 2018 to December 2020. Data collection was conducted online and through face-to-face interviews with the donors in their native language (Hebrew or Arabic). Results: Overall, 91 live kidney donors aged 18–49 years were enrolled. Of those, 65.9% were males, and 54.9% were academic donors. Among the live kidney donors, 59.3% reported that the motivation behind the donation was a first-degree family member vs. 35.2% altruistic and 5.5% commercial. Only 13.2% reported that the provided disclosure adequately explained the possible consequences of living with a single kidney. Approximately 20% of the participants reported that the disclosure included information regarding their risk of developing ESRD, hypertension, and proteinuria. The donors reported a low mean of the index score that indicates a low follow-up by the physician after the donation (mean = 1.16, SD = 0.37). The mean GFR level was significantly lower in the post-donation period one year following a kidney donation (117.8 mL/min/1.73 m2) compared with the pre-donation period (84.0 mL/min/1.73 m2), p < 0.001. Conclusion: Our findings display that donors’ satisfaction with the ethical competence of multi-professional nephrology teams regarding the disclosure of donation consequences to live kidney donors is low. This study indicates that donors are at an increased risk of worsening kidney functions (creatinine and GFR), and BMI. Our findings underscore the imperative to advise donors that their condition may worsen over time and can result in complications; thus, they should be monitored during short and long-term follow-up periods. This study was not registered.